Effects of UGT1A6 and GABRA1 on Standardized Valproic Acid Plasma Concentrations and Treatment Effect in Children With Epilepsy in China. Issue 6 (December 2016) - Feng, Weixing; Mei, Shenghui; Zhu, Leting; Yu, Yazhen; Yang, Weili; Gao, Baoqin; Wu, Xiaojuan; Zhao, Zhigang; Fang, Fang
Abstract : Background: Valproic acid (VPA) is a widely used antiepileptic drug with acceptable safety and efficacy in treating pediatric patients with various kinds of seizures. However, interindividual variations in plasma concentrations and treatment effects of patients with epilepsy treated with VPA are observed. This study aimed to evaluate the effects of various genetic variations on normalized plasma concentration of VPA (NCVPA) and the treatment response in Chinese children with epilepsy administered with VPA. Methods: Pediatric patients (3 months to 18 years old) with epilepsy, taking VPA therapy, were enrolled in the study. Important genetic variations of the pharmacokinetic and pharmacodynamic pathways of VPA were evaluated using the MassARRAY system (Sequenom). The associations of genetic variations with NCVPA/drug response and the mean value of NCVPA in responsive and resistant patients were evaluated using SPSS (17.0) and Plink (1.07) software. Results: A total of 111 children with epilepsy (80 responsive and 31 resistant) were enrolled. rs28898617 (UGT1A6, A > G) was associated with an increase in NCVPA (β = 5.31, 95% confidence interval = 0.78–9.83, P = 0.024); therefore, patients with this variation need a lower dose of VPA. rs2279020 (GABRA1, G > A) was associated with a decreased risk of developing VPA-resistant epilepsy (odds ratio = 0.42, 95% confidence interval = 0.21–0.84, P = 0.014). Similar NCVPA was observed in resistant and responsive patients ( P = 0.257). Conclusions: rs28898617 (UGT1A6, A > G) variation was associated with an increase in NCVPA. rs2279020 (GABRA1, G > A) variation was associated with a decreased risk of developing VPA-resistant epilepsy. Resistant and responsive patients to VPA treatment had a similar mean value of NCVPA. The findings may help clinicians to adjust the dose and predict treatment effect for children with epilepsy receiving VPA treatment. Abstract : Supplemental Digital Content is Available in the Text.